The Assessment of the Difficulty Index of Impacted Third Molar Based on Pederson’s Difficulty Index - Karamatullah; Hammad Wazir; Muhiyuddin Malik; Tahir Saeed; Maidah; Usman Ul Haq; Manzoor Khan; Muhammad Ilyas (Journal of Gandhara Medical and Dental Sciences)
OBJECTIVES